Research of Influence Modification of Natural Concentrate on Quality Metal; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Fedoseev S. N. Sergey Nikolaevich (2016, 2016)
Title screen